PENGARUH LEVEL KUNING TELUR PADA PENGENCER SUSU SKIM DAN LAMA WAKTU PENYIMPANAN TERHADAP MOTILITAS DAN ABNORMALITAS SPERMATOZOA AYAM KAMPUNG - Santoso, Ilham Budi; Saleh, Dadang Mulyadi; Mugiyono, Sigit (ANGON: Journal of Animal Science and Technology, 2020)
The purpose of this research was to determine the effect of the interaction between the addition of egg yolk levels in skim milk (P) diluents and storage time (W) on the motility and abnormalities of kampung rooster spermatozoa. The study used a completely randomized design (CRD) with a factorial pattern of 3 x 3 with a P factor (P0 = skim milk + 0% egg yolk, P1 = skim milk + 10% egg yolk, P2 = skim milk + 20% egg yolk) and a factor W (W1 = 10 minutes, W2 = 40 minutes, W3 = 70 minutes) at room temperature of each treatment was repeated three times. ANOVA test results showed that each of the interactions of the P and W factors had a very significant effect (P<0,01) on spermatozoa motility and the polynomial orthogonal test results showed a highly significant linear effect (P<0,01) on each treatment interaction P and W. The percentage of motility produced by P0W1, P1W1, P1W2, P2W1, and P2W2 treatments is above 50% so it is still suitable for IB use. The best treatment interaction was shown by the interaction of P1 (skim milk + 10% egg yolk) with W1, W2, and W3 on the motility of spermatozoa forming linear lines with the equation y = -0,484x + 82,93 and the coefficient of determination (R2) of 0,995. ANOVA test results did not show any significant effect (P> 0.05) on the interaction of P and W on spermatozoa abnormalities and each factor had its own effect. P treatment had a very significant effect (P<0,01) and formed a linear line with the equation Y = 0,009 x + 0,079 with a coefficient of determination (R2) of 0,915, while the W factor had a significant effect (p <0,05) but had no significant effect (P>0,05) both linearly and quadratically. Abnormalities resulting from all treatments are below 20% making it suitable for insemination. From the results of this research it can be concluded that kampung rooster spermatozoa treated with an additional 10% and 20% egg yolk level stored up to 40 minutes at room temperature are still suitable for insemination.